2019
DOI: 10.3390/molecules24112144
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Two-Dimensional Organic-Inorganic Halide Perovskites for Highly Efficient and Stable Photovoltaic Application

Abstract: Solar cells made of hybrid organic-inorganic perovskite (HOIP) materials have attracted ever-increasing attention due to their high efficiency and easy fabrication. However, issues regarding their poor stability remain a challenge for practical applications. Engineering the composition and structure of HOIP can effectively enhance the thermal stability and improve the power conversion efficiency (PCE). In this work, mixed two-dimensional (2D) HOIPs are systematically investigated for solar-power harvesting usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The carbon length of the organic amines and also the reaction temperature of the synthesis procedure are the factors affecting the morphology, stability, and PLQY of perovskite nanocrystals (NCs) [16,17]. To improve stability, the synthesis of 2D perovskite colloidal nanoparticles (NPs) with high PLQY has appealed widespread focus [18][19][20]. 2D perovskite (n = 1 − 6) QDs with 1-butylammonium as a long organic cation and an average size of 10 nm are synthesized for Br and I halides.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon length of the organic amines and also the reaction temperature of the synthesis procedure are the factors affecting the morphology, stability, and PLQY of perovskite nanocrystals (NCs) [16,17]. To improve stability, the synthesis of 2D perovskite colloidal nanoparticles (NPs) with high PLQY has appealed widespread focus [18][19][20]. 2D perovskite (n = 1 − 6) QDs with 1-butylammonium as a long organic cation and an average size of 10 nm are synthesized for Br and I halides.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many theoretical studies about 2D perovskite have been carried out. For instance, Dong et al [14] theoretically investigated the effects of mixed cations (Cs + and Rb+) and metal ions (Ge 2+ and Pb 2+ ) of (RNH 3 ) 2 (MA) n−1 B n X 3n+1 (n = 3) on the solar harvesting to electricity efficiency, demonstrating tuning appropriate composition ratio can improve efficiency and stability. Ding et al [15] reported that optical absorption and transport property of single-layer 2D perovskite Cs 2 PbI 4 are strongly depend on the layers n. Additionally, Bala et al [16] calculated electronic structure of multilayered 2D perovskite Cs n+1 Sn n−x I 3n+1 , and results reveal that band gaps, thermal stability and optical property of multilayered 2D perovskite vary with layer n.…”
Section: Introductionmentioning
confidence: 99%